The Effect of Bamboo Dacing Learning Model to Improve Mathematics Learning Outcomes - Dede Apriani; Eva Julianti; Laili Habibah Pasaribu (Universitas Islam Lamongan, 2025)
This study aims to determine the learning outcomes of mathematics in class VIII MTS Ponpes Darus Sholihin before and after using the Bamboo Dancing learning model. This research was a quasi-experiment involving two classes, each with 25 students. Data were collected through observation and tests. The results showed that the control class had an average pretest score of 67.72, while the experimental class, after treatment, had a posttest average of 85.76. Statistical analysis (sig = 0.000 < 0.05) confirmed a significant effect, meaning the Bamboo Dancing model improved learning outcomes. This model enhances engagement, understanding, and social skills, making it effective in mathematics learning.